2020
DOI: 10.18057/ijasc.2020.16.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Beam-to-Upright End Connections Steel Storage Systems

Abstract: This study presents an experimental and numerical research into the behavior of beam-to-upright end connections, which are part of steel storage systems. A total of 21 cantilever tests comprising three upright and four beam cross sections, were conducted, and a finite element numerical model was developed. The mod el was developed to compare its results with experimental results and to extrapolate these results in a parametric analysis. The aim of the study is to evaluate the behavior, semi-rigidity, and influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The main purpose of this research is to investigate the looseness that occurs in the tab connector in beam-upright connections and to evaluate the influence of looseness effect for the portal beam loaded with pallets, having different types of tab connectors at There are some published papers [5,6,9] which approach the experimental testing of the beam-to-upright end connections for steel storage system, with tab connectors, under bending loading, without considering the looseness effects. Investigations conducted on the rotation stiffness of the tab connections showed that the increasing of the height of the connector or the increasing of the number of the tabs of the connector, respectively, lead to the increasing of the connection rigidity [6,20], while the effect of the gap between the beam and the face of the tab connector could be neglected [20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main purpose of this research is to investigate the looseness that occurs in the tab connector in beam-upright connections and to evaluate the influence of looseness effect for the portal beam loaded with pallets, having different types of tab connectors at There are some published papers [5,6,9] which approach the experimental testing of the beam-to-upright end connections for steel storage system, with tab connectors, under bending loading, without considering the looseness effects. Investigations conducted on the rotation stiffness of the tab connections showed that the increasing of the height of the connector or the increasing of the number of the tabs of the connector, respectively, lead to the increasing of the connection rigidity [6,20], while the effect of the gap between the beam and the face of the tab connector could be neglected [20].…”
Section: Introductionmentioning
confidence: 99%
“…Typical connections used to assembly the uprights with beams, for the racking storage systems, are bolted connections [ 3 , 4 ] and connections with metal tabs [ 5 , 6 , 7 , 8 , 9 ]. Most research on such connections focuses on the analysis of rotational stiffness at ambient temperature [ 5 , 6 , 9 ] and high temperatures [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Steel storage racks play a critical role in the popularity of online shopping. At present, the research on steel storage racks mainly focuses on the structural performance of steel storage racks' members and components such as uprights [1][2][3][4][5], joints [6][7][8][9][10][11][12][13], and frames [14][15][16][17]. Typically, these investigations assume that the effects of the center of gravity and eccentricity of the load are disregarded.…”
Section: Introductionmentioning
confidence: 99%